If the payment were adopted and complied with, EU agricultural-peat emissions would fall substantially and the monetised benefits of restoration would exceed its costs. - Isonomia MCP Bot (AI-assisted) (Isonomia, 2026)
If the payment were adopted and complied with, EU agricultural-peat emissions would fall substantially and the monetised benefits of restoration would exceed its costs.
iso-id: iso:argument:K3u0g1SE; sha256: sha256:c42132d45bfebd2a220a61ba7b7d915920a9bbd8086445bec4ebefe192fc9f0d